“Sometimes I Feel Like Shakespeare...” (Intertextual Layers of “Pilgrims” by I. Brodsky) - O. V. Bogdanova; E. A. Vlasova (Научный диалог, 2021)
The article examines the well-known poem by I. Brodsky “Pilgrims” (1958), and offers a new, in-depth interpretation of it. The authors of the work focus on the “second” version of Brodsky’s text, supplemented in 1959 with an epigraph from a sonnet by W. Shakespeare. Starting from the epigraphic lines, the authors of the article instead of the generally accepted interpretation of the poem (through the traditional motif of the pilgrim’s wanderings as the endless movement of a person through life) bring to the fore the image (post)Shakespeare’s pilgrims-thoughts, pilgrims-feelings. Changing the perspective of perception allows them to see deeper layers of Brodsky’s poem and re-interpret already familiar images and motifs. Thus, the title lexeme of the text — “pilgrims” — is explained; the “strange” image of the “blue sun”, interpreted by critics as an element “from science fiction”, is reinterpret-ed; the semantics of the motif of the modern “bar”, read by researchers “as a symbol of mysterious foreign luxury”, is explained; the “unexpected” quotation in the text of a poem by N. Nekrasov, unloved by Brodsky, analyzed and explained; etc. Identification of broad intertextual layers of “Pilgrims” — poems by K. Balmont, V. Bryusov, F. Sologub, A. Akhmatova, O. Mandelstam, M. Lokhvitskaya, etc. — allows the authors of the work to demonstrate the multiplied potential of the poem, to in-crease the intensity of the tragic understanding of the world by the lyrical hero of Brodsky.